2021
DOI: 10.3390/cancers13040624
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Protein p53 and Inhibitor of Apoptosis Proteins in Colorectal Cancer—A Promising Signaling Network for Therapeutic Interventions

Abstract: Despite recent advances in the treatment of colorectal cancer (CRC), patient’s individual response and clinical follow-up vary considerably with tumor intrinsic factors to contribute to an enhanced malignancy and therapy resistance. Among these markers, upregulation of members of the inhibitor of apoptosis protein (IAP) family effects on tumorigenesis and radiation- and chemo-resistance by multiple pathways, covering a hampered induction of apoptosis/autophagy, regulation of cell cycle progression and DNA dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 180 publications
(217 reference statements)
0
18
0
Order By: Relevance
“…It is mutated in 50% of human cancers, including breast and colon. Its upregulation leads to induction of cell cycle arrest and apoptosis [ 66 , 67 ]. Although MDA MB-231 cells carry a mutated p53 gene (R280K mutation), mechanistic studies demonstrated that treatment with anticancer agents inducing p53-dependent intrinsic apoptosis (6-gingerol) resulted in p53 expression and quick apoptosis execution, supporting the hypothesis that p53 in MDA MB-231 is indeed a gain-of-function mutant [ 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is mutated in 50% of human cancers, including breast and colon. Its upregulation leads to induction of cell cycle arrest and apoptosis [ 66 , 67 ]. Although MDA MB-231 cells carry a mutated p53 gene (R280K mutation), mechanistic studies demonstrated that treatment with anticancer agents inducing p53-dependent intrinsic apoptosis (6-gingerol) resulted in p53 expression and quick apoptosis execution, supporting the hypothesis that p53 in MDA MB-231 is indeed a gain-of-function mutant [ 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the p53 gene is the gene with the highest correlation with human tumors so far, and its correlation with colon cancer has been widely studied and reported. 2 , 3 , 16 However, in colon cancer, the relationship between p53 pathway-related genes and patient prognosis is still unclear. In our study, we identified 3 ( CDKN2A, BAK1, BTG1 ) genes that are significantly related to PFS, and we believe that CDKN2A gene is an independent prognostic factor for PFS.…”
Section: Discussionmentioning
confidence: 99%
“… 2 It has been proven to play an important role in the process of colon adenoma canceration. 3 The protein encoded by the p53 gene is a transcription factor, which is mainly distributed in the cell nucleus and can specifically bind to DNA to control the initiation of the cell cycle. 4 The normal biological function of p53 is like a “genome guardian”.…”
Section: Introductionmentioning
confidence: 99%
“…Since the p53 family proteins are involved in a plethora of cell signaling pathways that regulate processes such as survival, proliferation, differentiation, apoptosis, and motility of both healthy and cancer cells [4,[296][297][298], it is of no surprise that particular isoforms are implicated in CRC as well (Table 1). However, to our knowledge, roles of the p53 isoforms have still not been investigated thoroughly in CRC (Figure 6).…”
Section: Involvement Of the P53/p73 Isoforms In Crc Development And Progressionmentioning
confidence: 99%